2022
DOI: 10.1002/jpln.202200062
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics persist in an arable soil but do not affect soil microbial biomass, enzyme activities, and crop yield

Abstract: Background: Microplastics (MP, plastic particles <5 mm) are ubiquitous in arable soils due to significant inputs via organic fertilizers, sewage sludges, and plastic mulches. However, knowledge of typical MP loadings, their fate, and ecological impacts on arable soils is limited. Aims:We studied (1) MP background concentrations, (2) the fate of added conventional and biodegradable MP, and (3) effects of MP in combination with organic fertilizers on microbial abundance and activity associated with carbon (C) cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 94 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Schöpfer et al. (2022), in this issue, found ≈ 300 plastic particles < 0.5 mm per kg in an agricultural soil that had not been treated with any of the materials listed above. They concluded that there are diffuse sources of microplastic that have not been identified so far.…”
Section: Editorialmentioning
confidence: 95%
“…Schöpfer et al. (2022), in this issue, found ≈ 300 plastic particles < 0.5 mm per kg in an agricultural soil that had not been treated with any of the materials listed above. They concluded that there are diffuse sources of microplastic that have not been identified so far.…”
Section: Editorialmentioning
confidence: 95%